Downregulation of miR‐145‐5p contributes to hyperproliferation of keratinocytes and skin inflammation in psoriasis. (1st February 2019) - Yan, J.J.; Qiao, M.; Li, R.H.; Zhao, X.T.; Wang, X.Y.; Sun, Q.
Summary: Background: The extensive involvement of microRNAs (miRNAs) in the pathogenesis of psoriasis is well documented. However, little is known about the contribution of specific miRNAs to the prevalence of this disease. Objectives: To explore the role of miR‐145‐5p in psoriasis. Methods: miRNA microarray analysis was performed in four patients with psoriasis and four controls. Quantitative reverse‐transcriptase polymerase chain reaction and fluorescence in situ hybridization were used to identify the dysregulated miRNAs. Luciferase assays were performed to determine whether miR‐145‐5p targets mixed‐lineage kinase (MLK)3. CCK‐8 assay and Magnetic Luminex Assay were performed to measure cell proliferation and chemokine secretion. Western blot analysis was used to investigate the protein levels of MLK3 and its downstream effectors. Mouse models of psoriasis were established for in vivo experiments. Results: miR‐145‐5p was downregulated in psoriatic lesional skin. Luciferase assays showed that MLK3 is a direct target of miR‐145‐5p. Overexpression of miR‐145‐5p in normal human epidermal keratinocytes (NHEKs) suppressed cell proliferation and secretion of chemokines. In contrast, silencing miR‐145‐5p promoted NHEK proliferation and increased chemokine secretion. Silencing MLK3 abrogated miR‐145‐5p inhibitor‐induced promotion of cell proliferation and chemokine expression. miR‐145‐5p regulates nuclear factor‐κB and signal transducer and activator of transcription 3 by targeting MLK3. Delivery of agomiR‐145‐5p into the skin decreased epidermal hyperplasia and ameliorated psoriasis‐like dermatitis. Delivery of antagomiR‐145‐5p led to the opposite effects. Conclusions: Our findings indicate that miR‐145‐5p negatively regulates proliferation and chemokine secretion of NHEKs by targeting MLK3, and downregulation of miR‐145‐5p contributes to skin inflammation in psoriasis lesions.